An Illusion of Self‐Sufficiency for Learning About Artifacts in Scaffolded Learners, But Not Observers. Issue 4 (17th January 2021) - Richardson, Emory; Sheskin, Mark; Keil, Frank C.
Abstract : Two studies ask whether scaffolded children ( n  = 243, 5–6 years and 9–10 years) recognize that assistance is needed to learn to use complex artifacts. In Study 1, children were asked to learn to use a toy pantograph. While children recognized the need for assistance for indirect knowledge, 70% of scaffolded children claimed that they would have learned to use the artifact without assistance, even though 0% of children actually succeeded without assistance. In Study 2, this illusion of self‐sufficiency was significantly attenuated when observing another learner being scaffolded. Learners may fail to appreciate artifacts' opacity because self‐directed exploration can be partially informative, such that learning to use artifacts is typically scaffolded instead of taught explicitly.